2007
DOI: 10.1111/j.1365-2583.2007.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

piggyBac‐based insertional mutagenesis in Tribolium castaneum using donor/helper hybrids

Abstract: We describe an efficient method for generating new piggyBac insertions in the germline of F(1) hybrid Tribolium castaneum derived from crosses between transgenic helper and donor strains. Helper strains carried single Minos elements encoding piggyBac transposase. The donor strain carried a single piggyBac element inserted into an actin gene, expanding the eye-specific, 3xP3-EGFP (enhanced green fluorescent protein) reporter expression domain to include muscle. Remobilization of the donor element is accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 40 publications
2
86
0
Order By: Relevance
“…2), allowing efficient genetic screens by means of chemical mutagens, radiation and binary transposon systems 3 . As in Caenorhabditis elegans, RNA interference (RNAi) is systemic in Tribolium, facilitating knockdown of specific gene products in any tissue, developmental stage or offspring of double-stranded (ds)RNA-injected females 4,5 .…”
mentioning
confidence: 99%
“…2), allowing efficient genetic screens by means of chemical mutagens, radiation and binary transposon systems 3 . As in Caenorhabditis elegans, RNA interference (RNAi) is systemic in Tribolium, facilitating knockdown of specific gene products in any tissue, developmental stage or offspring of double-stranded (ds)RNA-injected females 4,5 .…”
mentioning
confidence: 99%
“…S3), which is probably an underestimate, because genome regions that cannot be assembled are enriched in repeats. Both genomes contain copies of the piggyBac transposon (234 total and 6 with intact ORFs in C. floridanus, 976 total and 23 with intact ORFs in H. saltator), which has been used for insect transgenesis (6,7), and may also prove useful in ants.…”
mentioning
confidence: 99%
“…Among these tools is a sequenced and well-annotated genome (Tribolium Genome Sequencing Consortium et al 2008), which provides the necessary sequences for Cas9 targeting. Furthermore, a number of essential genes have been identified (Lorenzen et al 2007;Trauner et al 2009;Ulrich et al 2015), and their RNAi phenotypes characterized by the iBeetle Project (Ulrich et al 2015), establishing which candidate genes are the most efficient to target for population reduction.…”
Section: The Red Flour Beetle: a Worldwide Pest Of Stored Grainsmentioning
confidence: 99%
“…For example, a piggyBac transposon that contains the enhanced green fluorescent protein (EGFP) gene inserted very close to the Medea-1 element (∼1 centiMorgan away) (Lorenzen et al 2008), has been shown to be inherited at super-Mendelian rates (5-fold higher than predicted) (Lorenzen et al 2007). Medea might also provide a more stable and reliable gene-drive mechanism than Cas9-based systems, and efforts are currently underway in the Lorenzen lab to clarify this element's mode of action, and to develop its use for pest control.…”
Section: The Red Flour Beetle: a Worldwide Pest Of Stored Grainsmentioning
confidence: 99%